Rattus argentiventer - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
671. Ricefield Rat Rattus argentiventer French: Rat des rizieres / German: Reisfeldratte / Spanish: Rata de arrozal Taxonomy. Epimys rattus argentiventer H. C. Robinson & Kloss, 1916, Pasir Ganting, west coast of Sumatra, Indonesia. R. argentiventer is in the R. rattus species group, although additional sampling of lessstudied species is needed to fully resolve its placement and that of other species in the genus. Monotypic. Distribution. C Laos, Vietnam, C & S Cambodia, SC Thailand, Malay Peninsula, Singapore, Sumatra, Borneo, Java, Bali, and many smaller offshore Is. Introduced into the Philippines (Luzon, Mindoro, Negros, Cebu, and Mindanao Is), Sulawesi, Lesser Sundas (Lombok, Sumbawa, Sangeang, Komodo, Rintja, Flores, Adonara, Lembata, Alor, Sumba, Timor, and Tanimbar Is), New Guinea, and possibly Seram I. Descriptive notes. Head-body 136-230 mm, tail 149-210 mm, ear 16-24-5 mm, hindfoot 30-41 mm; weight 52-239 g. The Ricefield Rat is medium-sized and similar to the Losea Rat (R. losea), although it ismuch larger and has an extra pair of mammae. Pelage is sleek and moderately spiny. Dorsum is orangish brown, speckled black throughout, and most individuals have distinctive orangish brown patch in front of each ear that can fade in older individuals. Venter is silvery white to dull gray; dark streak runs lengthwise ventrally. Feet are long and narrow, with broad band of dark hairs dorsally and white on sides and digits. Ears are relatively long and rounded, being lightly furred and similar in color to dorsum;vibrissae are relatively long. Tail is 80-120% of head-body length (usually ¢.100%) and is generally unicolored brown. Skull has larger bulla than in the Roof Rat (R. raftus). There are six pairs of mammae: three axillary and three inguinal pairs. Chromosomal complementis 2n = 42, FN = 61. Habitat. Various open grassland areas and swampy grasslands. Today, the Ricefield Rat is found primarily in agricultural fields (rice specifically), grasslands, and plantations, being relatively commensal with ...